Intercropping sorghum and soybean efficiency using contour ridges technology in southern Mali - Dembélé, C.O.; Traoré, K.; Karembe, M.; Zemadim, Birhanu; Traoré, B.; Cisse. F.; Samake, O. (Canadian Center of Science and Education, 2022)
Kani and Noumpinesso are two neighboring villages in which soil degradation is mainly caused by runoff and erosion. Contour ridges tillage (CRT) was identified as a runoff and erosion controlling technology while improving soil moisture and nutrient availability for crops. CRT technology associated with sorghum and soybean based intercropping system was assessed during 2017 and 2018 cropping season in an experiment under split plot design. Intercropping systems highly increased sorghum and soybean growth and yields. Sorghum grain yield, biomass yield, height and diameter were increased by 62, 51, 22 and 19%, respectively by intercropping. Soybean grain yield, biomass yield, height and diameter increased by 47, 30, 25 and 25%, respectively. Intercropping sorghum with soybean had an advantage with a Land Equivalent Ratio (LER) of 1.54 and 1.44 in 2017 and 2018 respectively. The technology of CRT added 40, 39, 25 and 21% on sorghum grain yield, straw yield, height and diameter respectively. The same parameters with soybean were greater by 52, 48, 38 and 35%, respectively. The application of CRT was economically profitable with a Value to Cost Ratio (VCR) of 3.3 and 3.0 in sorghum production and 12.8 and 9.2 in soybean production during 2017 and 2018 respectively.